2017
DOI: 10.1038/nature23883
|View full text |Cite
|
Sign up to set email alerts
|

m6A modulates haematopoietic stem and progenitor cell specification

Abstract: N-methyladenosine (mA) has been identified as the most abundant modification on eukaryote messenger RNA (mRNA). Although the rapid development of high-throughput sequencing technologies has enabled insight into the biological functions of mA modification, the function of mA during vertebrate embryogenesis remains poorly understood. Here we show that mA determines cell fate during the endothelial-to-haematopoietic transition (EHT) to specify the earliest haematopoietic stem/progenitor cells (HSPCs) during zebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
505
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(530 citation statements)
references
References 52 publications
16
505
1
1
Order By: Relevance
“…It was also shown that the embryonic METTL3 function in the haematopoietic system is mediated by the YTHDF2 dependent decay of Notch encoding mRNA [66]. Similar results were obtained upon conditional METTL3 KO in the mouse AGM region [67], therein, indicating an evolutionally conserved function of METTL3 in HSPCs (haematopoietic stem and progenitor cells) specification in vertebrates.…”
Section: M6a Roles In Aml (Acute Myeloid Leukaemia) and Normal Haementioning
confidence: 59%
See 1 more Smart Citation
“…It was also shown that the embryonic METTL3 function in the haematopoietic system is mediated by the YTHDF2 dependent decay of Notch encoding mRNA [66]. Similar results were obtained upon conditional METTL3 KO in the mouse AGM region [67], therein, indicating an evolutionally conserved function of METTL3 in HSPCs (haematopoietic stem and progenitor cells) specification in vertebrates.…”
Section: M6a Roles In Aml (Acute Myeloid Leukaemia) and Normal Haementioning
confidence: 59%
“…Downregulation of METTL3 in zebrafish embryos and in the mouse aorta-gonad-mesonephros (AGM), the region of the primary origins of the definitive HSC in vertebrates, strongly affect HSC production by repressing Notch signaling [66]. It was also shown that the embryonic METTL3 function in the haematopoietic system is mediated by the YTHDF2 dependent decay of Notch encoding mRNA [66].…”
Section: M6a Roles In Aml (Acute Myeloid Leukaemia) and Normal Haementioning
confidence: 99%
“…Here, we establish a novel link between TARBP2 intronic binding, m 6 A methylation, and controlled intron retention leading to transcript degradation in the nucleus. Although RNA methylation marks impact a variety of developmental and disease processes (Zhang et al, 2017a(Zhang et al, , 2017b (which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 99%
“…112 The same RNA signature can exert powerful effects on progenitor cell specificity and function. 113 More recently, Werner et al 114 described a unique class of lncRNAs based on their chromatin-binding features known as cheRNAs. The CheRNA HIDALGO (hemin-induced cheRNA downstream of fetal hemoglobin) stimulates the fetal HBG1 gene during erythroid differentiation by promoting contacts to a downstream enhancer.…”
Section: Knockout Mouse Generationmentioning
confidence: 99%